Decoding Hip Muscle Activation: A Comparative Electromyographic Analysis of Turn-Out Bent Knee Pulse and Single-Leg Banded Glute Bridge Exercises in Healthy Female Subjects - Qais Gasibat; Cristina Ioana Alexe; Gabriela Raveica; Dragoș Ioan Tohănean; Koronas Vasilios; Dan Iulian Alexe (MDPI AG, 2023)
Individuals with lower extremity injuries and back pain may exhibit weakness and stiffness in important muscles such as the gluteus maximus and external hip rotators. To aid clinicians in understanding the impact of exercises on factors like stability, endurance, and strength, electromyography (EMG) examination can be employed to monitor muscle activation. In this investigation, the EMG activity of the gluteus maximus and medius were compared between two exercises: the turn-out bent knee pulse and the single-leg banded glute bridge. The study enrolled a group of 64 healthy young women, aged 19 to 24 years. The raw data collected were standardized and represented as a percentage of maximum voluntary isometric contraction (%MVIC). To assess the reliability of the EMG recordings, the test-retest analysis was performed using the intraclass correlation coefficient (ICC3,1). Statistical analysis involved conducting a one-way ANOVA to compare the EMG amplitudes between the two exercises. Remarkably, the results demonstrated a significantly higher EMG signal amplitude during the single-leg banded glute bridge exercise (mean ± SD: 90 ± 28% MVIC) when compared to the turn-out bent knee pulse exercise (mean ± SD: 70 ± 15% MVIC) (F = 16.584, p = 0.001). The study found that the single-leg banded glute bridge exercise had a significantly higher EMG signal amplitude compared to the turn-out bent knee pulse exercise. This suggests that the single-leg banded glute bridge exercise may be more effective in strengthening the gluteus maximus and medius muscles. Overall, this study highlights the importance of targeted muscle training in rehabilitation protocols and the use of EMG examination to monitor muscle activation.